Fixação do enxerto ósseo autógeno em bloco com adesivos a base de cianoacrilato ou parafuso de titânio: estudo histológico em coelhos - Rocha, Julierme Ferreira [UNESP] (2015)
Cyanoacrylates are used in oral and maxillofacial surgery for closure of surgical wounds, oroantral communication, cleft lip repair, and osteosynthesis of the craniofacial skeleton. The aim of this study was compare three fixation methods (ethyl-cyanoacrylate, n-butyl cyanoacrylate or titanium screw) of autogenous onlay bone graft (AOBG). Bilateral ostectomies were made in the parietal region in thirty rabbits using a 6-mm-diameter trephine. The AOBG was fixed with ethyl-cyanoacrylate (Group I), n-butyl cyanoacrylate (Group II) or titanium screw (Group III - control). The animals were sacrificed at five, fifteen, thirty, sixty, and one hundred and twenty days, and the samples were obtained from AOBG region. The processing was done in accordance with the method histotechnical and stained with hematoxylin and eosin. The evaluated histological events were: inflammatory infiltrate, adhesive resorption and bone formation and bone resorption. The results of cellular events were subjected to the Kruskal-Wallis test followed by Dunn's test to determine differences between groups (p <0.05). The qualitative numerical analysis showed the presence of inflammatory infiltrate and significant bone resorption in groups I and II, especially in the early periods. The inflammatory infiltrate seen in the control group was discrete (p <0.05). The adhesive reabsorption process was similar, with no statistical difference (p> 0.05). After 120 days, we observed residual adhesive between AOBG ...